2021
DOI: 10.1371/journal.pone.0251144
|View full text |Cite
|
Sign up to set email alerts
|

Differential rotational movement and symmetry values of the thoracolumbosacral region in high-level dressage horses when trotting

Abstract: High-level dressage horses regularly perform advanced movements, requiring coordination and force transmission between front and hind limbs across the thoracolumbosacral region. This study aimed at quantifying kinematic differences in dressage horses when ridden in sitting trot–i.e. with additional load applied in the thoracolumbar region–compared with trotting in-hand. Inertial sensors were glued on to the midline of the thoracic (T) and lumbar (L) spine at T5, T13, T18, L3 and middle of the left and right tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Most inertial sensor-based studies focus on capturing measures of limb lameness with little to no regard for the potential confounding effects of axial skeleton pain or dysfunction [ 55 , 56 ]. Typical inertial sensor placement is on the dorsum of the head and pelvis [ 35 ]; therefore, it is expected that altered head and pelvic displacement due to axial skeleton pain or stiffness would directly affect measures of limb lameness [ 57 , 58 ]. The large variability in the reported vector sum values for the forelimbs supports this.…”
Section: Discussionmentioning
confidence: 99%
“…Most inertial sensor-based studies focus on capturing measures of limb lameness with little to no regard for the potential confounding effects of axial skeleton pain or dysfunction [ 55 , 56 ]. Typical inertial sensor placement is on the dorsum of the head and pelvis [ 35 ]; therefore, it is expected that altered head and pelvic displacement due to axial skeleton pain or stiffness would directly affect measures of limb lameness [ 57 , 58 ]. The large variability in the reported vector sum values for the forelimbs supports this.…”
Section: Discussionmentioning
confidence: 99%
“…These were used as part of a sensor-based system (Xsens MTw Awinda), which has been validated for translational displacements derived from internal tri-axial sensor accelerations, which were then rotated into a horse-based reference frame based on the sensor orientation estimate and then double integrated into the displacement [ 16 , 18 ]. Data processing methods have been described elsewhere [ 19 , 20 ]. In brief, orientation-time signals for differential axial rotation, flexion-extension, and lateral bending values of T5, T13, L3, and TS were used to calculate differential rotational movement, as described by MacKechnie-Guire and Pfau 2021a, 2021b [ 2 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies that have used the Xsens ® technology to study the biomechanics of the equine pelvic, thoracic, and lumbar regions have demonstrated that the saddle and the rider have a significant effect on the kinematics of the equine spine. MacKechnie-Guire et al [ 85 ] reported changes in the thoracolumbosacral region of dressage horses when ridden in sitting trot as compared to trotting in hand. Increased range of motion (ROM) was found in the caudal thoracic and lumbar regions (T18-L3) in sitting trot.…”
Section: Horse–rider Interaction and Imusmentioning
confidence: 99%
“…Increased range of motion (ROM) was found in the caudal thoracic and lumbar regions (T18-L3) in sitting trot. Cranial thoracic motions remained unchanged, but heading rotational values declined [ 85 ]. In another study, the ROM of the caudal thoracic and thoracolumbar regions decreased by −1.3 (0.4)° and −0.6 (0.2)°, respectively, while protraction and retraction angles increased during rising trot as compared to trotting in hand.…”
Section: Horse–rider Interaction and Imusmentioning
confidence: 99%